Searching for Rural Development : Labor Migration and Employment in Mexico - Grindle, Merilee S. (Food Systems and Agrarian Change, 2019)
Throughout the Third World, rural people must leave their homes in ever greater numbers to seek temporary work in urban centers, in distant rural areas, or across international borders. This temporary labor migration, less an option than a necessity for many, is symptomatic of rural stagnation and increasing economic dependence and is most prevalent in regions where the base for agricultural development is poor. Searching for Rural Development addresses the critical question of how rural development strategies can help provide more secure livelihoods for the millions who are now unable to sustain themselves and their families in local communities. Focusing on Mexico, Merilee S. Grindle examines how rural families adapt to the paucity of local employment opportunities by pursuing complex strategies of income diversification. She assesses various options for creating jobs in rural and semirural areas and considers how recommended rural development policies can be implemented through the political process.